Effects of GABA/β-glucan supplements on melatonin and serotonin content extracted from natural resources - Dutta, Sayan Deb (PLoS One, 2021)
OBJECTIVE: This study aimed to monitor the secretion of serotonin and melatonin in the blood serum of rats in the presence of rice bran (RB), and Sarcodon aspratus (S) extracts for sleep promotion. BACKGROUND: Sleep is a natural physiological phenomenon, and sleep disorders may cause severe mental hazards leading to excessive daytime sleepiness (EDS). The γ-aminobutyric acid (GABA) and β-glucan are the essential active ingredients of RB and mushroom, respectively, exhibited stress-reduction and nerve stabilizing potential through regulation of melatonin and serotonin hormones. METHODS: Cytotoxicity of the extracts (RBS) was evaluated through WST-1 assay. The melatonin and serotonin concentrations in the blood serum were measured through ELISA kits. The Ig ELISA kit measured the immunoglobulin’s (IgG, IgM, and IgA) concentrations. RESULTS: Improved cell viability was observed in RBS treated groups than control, indicating their biocompatibility. The melatonin and serotonin levels were high in RBS (5:5 and 7:3) treated groups compared to the control. Enhanced expression of immunoglobulin (Ig) A and G level was observed in RBS treated rats. The serotonergic genes (5-HTT, 5-HT 1B, and MAO-A) expression levels were upregulated in RBS treated groups vis-à-vis the control. CONCLUSION: Based on these results, we anticipated that RBS supplements could promote the sleep phenomenon by elevating the serotonin/melatonin level in the blood through the serotonergic system. Therefore, RBS supplements can be utilized as functional food material for sleep promotion.